Pengaruh Kompetensi dan Profesional Auditor terhadap Kualitas Audit pada Kantor Akuntan Publikdi Wilayah Jakarta Selatan - Umar Tauhid; Denok Sunarsi (Jurnal Neraca Peradaban, 2021)
This study aims to determine the effect of auditors' competence and professionalism on audit quality at the public accounting firm in South Jakarta. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, competence has a significant effect on audit quality by 53.1%, the hypothesis test obtained t count> t table or (7,746> 2,006). Professional auditors have a significant effect on audit quality by 43.8%, hypothesis testing is obtained t count> t table or (6.433> 2.006). The competence and professionalism of auditors simultaneously have a significant effect on audit quality with the regression equation Y = 7,236 + 0.430X1 + 0.393X2 and the influence contribution is 63.1%, the hypothesis test is obtained F count> F table or (44.431> 2.780).